Efficient and low-complexity matrix inversion scheme for massive multiple-input multiple-output systems using rapid numerical algorithms - Mukubwa, Emmanuel; Sokoya, Oludare A (Journal of engineering (Stevenage, England), 2019)
Performances of the regularised zero forcing (RZF) precoder, rapid numerical algorithm (RNA) precoder and the truncated polynomial expansion (TPE) Precoder are compared and analysed for massive multiple-input multiple-output (MIMO) wireless system in a downlink scenario. The achievable data rates, bit error rates and signal-to-interference-to-noise ratio were investigated. The simulated results agree with the theory of massive MIMO system. Also, the RZF precoder and the RNA precoder perform better in comparison to TPE precoder.